HYPODONTIA IN CHILDREN WITH AND WITHOUT CLEFT LIP AND PALATE - A CASE CONTROL STUDY - Ravi, Hanshika; Ravindran, Vignesh; Prabu, Dinesh (International Journal of Psychosocial Rehabilitation, 2020)
Hypodontia is a cranial malformation characterized by congenital missing teeth. It is seen increased in cleft lip patients.It affects the tooth bud at the early to later stages of tooth development.This study was conducted to evaluate and compare the presence of hypodontia in children with and without cleft lip and palate.89000 case sheets were reviewed from the dental treatment records for presence of hypotonia in children with and without cleft lip and palate from June 2019-March 2020. Inclusion criteria included patients above 3 years and below the age of 18 years with the presence of cleft lip and palate.The final sample size consists of 10 patients divided into two groups: 5 patients with cleft lip and palate and 5 patients without cleft lip and palate. Data was analysed using SPSS software, and the Mann-Whitney-U test was done. The results showed that none of the cases with cleft lip and palate had hypodontia. Within the limitations of the study, there was a lesser prevalence of hypodontia in children with cleft lip and palate when compared to children without cleft lip and palate.